The Role of Guidance Counselling in Students’ Career Development - Baiq Susan Hariani (Journal of Educational Studies, 2025)
This article discusses the important role of counseling guidance in students' career development. With a focus on educational context, the article outlines how counseling guidance services can make a significant contribution to students' self-understanding, clarification of career options, and development of skills and strategies relevant to the world of work. Through a holistic approach, counseling guidance helps students identify their personal interests, talents, and values, which in turn form the basis of decision-making regarding career choices. The article also highlights the role of counselors in providing information about job market trends, job opportunities, and preparation for challenges in the professional world. Thus, this study emphasizes how essential the role of counseling guidance is in helping students understand and develop their careers along with the development of the dynamic world of work. Career is an important aspect in a person's life, which affects not only income, but also overall quality of life. Many factors influence career development, and Guidance and Counseling (BK) plays an important role in helping individuals live a successful career journey. This article will explain the role of counselors in career development, the methods used in this process, and will detail some pertinent references to support this understanding.